The Arabs in Iran between the Pahlavi and the Republican era 1925-1980 (Journal of the College of Basic Education, 2023)
Summary of the research:Arabs live in the southwestern parts of Iran, and their areas of residence are called (Arabistan). Arabs ruled their lands since ancient times, and Arabistan is one of the most important strategic locations in Iran, where oil and gas wells and other natural resources prompted Shah Reza Pahlavi to occupy it and make it subordinate to the central government, and he followed a policy of demographic change in Arabistan. The Arabs were also unable to enjoy their wealth and goods, which prompted them to struggle against the Pahlavi regime, and they had a decisive role in the revolution that ended the Pahlavi rule. The Arabs hoped well in the new system to achieve their legitimate demands and within the system of the Islamic state, but they were met with categorical rejection, and their will was not respected, so they followed the path of struggle to achieve the demands.Keywords: Iran - Arabistan - Arabs